2018
DOI: 10.1021/acs.jpcc.8b02734
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of [(CH3)2NH2][Zn(HCOO)3] Hybrid Perovskite Containing Different Nitrogen Isotopes

Abstract: We present a combined differential scanning calorimetry (DSC) and infrared (IR), Raman, electron paramagnetic resonance (EPR), and NMR spectroscopy study of dimethylammonium zinc formate frameworks [(CH 3 ) 2 NH 2 ][Zn(HCOO) 3 ] containing 14 N and 15 N nitrogen isotopes. The DSC reveals very small differences in the phase-transition temperatures for both compounds. The IR and Raman spectroscopies indicate different frequencies of the vibrational modes that involve a nitrogen atom. The temperature-dependent IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…[36] for nphoton transitions should have been too heavy to implement and unnecessary. Due to the large zfs expected in this family of compounds 5,12 , only the 1-photon transitions are expected to occur(nphoton transitions are expected when D ∼ h mw 37 with h mw the microwave field ). Using the first order Fermi golden rule, the Rabi frequency of a transition m to n is…”
Section: Rabi Distribution Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…[36] for nphoton transitions should have been too heavy to implement and unnecessary. Due to the large zfs expected in this family of compounds 5,12 , only the 1-photon transitions are expected to occur(nphoton transitions are expected when D ∼ h mw 37 with h mw the microwave field ). Using the first order Fermi golden rule, the Rabi frequency of a transition m to n is…”
Section: Rabi Distribution Calculationmentioning
confidence: 99%
“…Nevertheless, the crystal field parameters are in the range of what is expected for this family of material. 12 The crystal field distribution ∆D is about 50 MHz, much less than the one needed to simulate the HT phase. In the LT phase, the DMA + cations now have only one possible orientation induced by the ferroelastic phase.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…HOIs have been stabilized with various organic functional groups, such as halides, formates, dyanides, dicyanamides, amides and dicyanometallates [1,7,8]. Ferroelectric properties have been explored for [(CH 3 ) 2 NH 2 ][M(HCOO) 3 ] with M=Mg, Fe, Co, Ni, Cu, or Zn, where polarizations in the range 0.6 μC cm −2 -6 μC cm −2 have been observed [9][10][11][12][13]. The magnitude of polarization is not as high as prototypical ferroelectric oxides, e.g., 50 μC cm −2 and 66 μC cm −2 for Bi 4 Ti 3 O 12 and PbTiO 3 , respectively [14,15], yet might be promising for bio-imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…We have chosen the DMA + cation due to its wellknown properties in the perovskite-like MOFs with the framework composed of only one type of divalent metal ions. [9][10][11][12][13][14][15][16][17] These studies have revealed plenty of interesting phenomena depending on the metals building the metal-formate framework, including multiferroicity, 9,10,12 ferroelectricity, 16 magnetic 12,13,15 or dielectric 13,14 properties. In the present study we have decided to explore how some properties can be tuned when divalent metal ions are substituted by a mixture of monoand trivalent metal ions in the perovskite-type structure.…”
Section: Introductionmentioning
confidence: 99%